Impacto da pandemia de Covid–19 nos casos de tuberculose e encerramentos por cura, abandono e óbito no município de Fortaleza, Ceará. - Permanbuco, Marília Lopes (2023)
The aim of the study was to describe the sociodemographic and epidemiological profile of Tuberculosis (TB) cases by analyzing the levels of cure, abandonment, and death among patients treated in the Basic Health Units of the municipality of Fortaleza, Ceará, during the pre-pandemic period (2011 to 2019) and the Covid-19 pandemic (2020 and 2021). Additionally, it aimed to characterize TB-Covid coinfection-related deaths. A cross-sectional study was conducted as part of the "Operationalization of Tuberculosis Control in Basic Health Units" project. Data were collected from TB cases reported between 2010 and 2021 through the epidemiological surveillance of the Municipal Health Department of Fortaleza, including all Covid-19 cases diagnosed via laboratory testing (RT-PCR) with confirmed deaths reported from January 2020 to December 2021. Temporal trends were analyzed using trend lines, linear equations, and determinant coefficients (R²). The cure, abandonment, and death rates, in general, deviated from the standards established by the World Health Organization, indicating unsatisfactory percentages and declining rates of successful treatment, along with an increase in abandonment and death rates exacerbated by the Covid-19 scenario. Furthermore, 129 Covid19 deaths were reported among TB cases, representing 0.6% of Covid-19 deaths during the period, with an upward trend over time and a peak in outcomes from February to May 2021. Regarding sociodemographic characteristics, the periods showed similarities with a predominance of males, age groups of 21 to 40 and 41 to 60 years, mixed race, and incomplete 5th to 8th-grade education, followed by incomplete 1st to 4th-grade education. Concerning clinical characteristics, pulmonary TB continued to be prominent. In the extrapulmonary category, pleural TB predominated in both periods, although peripheral lymph node TB, meningoencephalic TB, miliary TB, and bone TB deserve attention. Alcoholism was a common comorbidity in both periods, followed by Aids and diabetes. Weaknesses were observed in data completeness regarding pharmacological treatment and the performance of diagnostic tests such as chest X-rays, rapid tests, sputum smear microscopy, histopathology, and culture. This highlights the challenges related to the overload of healthcare systems and the neglect of routine interventions for other health conditions and comorbidities. Consequently, underreporting of cases and issues related to TB management in the municipality of Fortaleza are evident, exacerbated during the Covid-19 pandemic, potentially impacting population health and TB control. These findings support the need for further research, including population-based studies, and the formulation of public policies aimed at mitigating the impact of Covid-19 on TB.